Studies on harvest maturity of Mallika and Amrapali mango cultivars grown under the submontane region of Himachal Pradesh - Sharma, Shashi K. (Indian Journal of Horticulture, 2010)
Amrapali and Mallika are the newly introduced mango cultivars in the low hill regions of Himachal Pradesh. The studies were conducted for the standardization of optimum fruit maturity for harvesting of these cultivars under the low hill conditions (400 to 1000 m a.m.s.l.) of the state. It has been concluded from the studies that at lower altitudes (upto 700 m), Mallika cultivar attained harvest maturity during 2nd week of August and at higher altitudes it became ready for harvesting by 3rd week of August. Amrapali cultivar attained harvest maturity by 2nd week of August in this region irrespective of the altitudinal variation. Quality was not much affected due to location.